Budd-Chiari syndrome-acute-on-chronic liver failure with simultaneous thrombotic and non-thrombotic acute insults - Vinay Borkar; Mit Shah; Chintan Tailor; Shamshersingh Chauhan; Saiprasad Lad; Vikramaditya Rawat; Yatin Lunagariya; Shivani Chopra; Deepak Sasikumar; Meghraj Ingle (Society of Gastrointestinal Intervention, 2024)
A 21-year-old man presented with acute onset of jaundice, abdominal pain, ascites, and hepatomegaly, along with a history of Budd-Chiari syndrome previously treated with vena cava angioplasty. Investigations revealed rapidly worsening jaundice, coagulopathy, elevated creatinine levels, reactive hepatitis B serology, and positive antiphospholipid antibodies, with scores indicating a poor prognosis for liver transplant-free survival. Abdominal computed tomography demonstrated a narrowed intrahepatic vena cava and new thrombosis in the right and middle hepatic veins. Renal biopsy, prompted by nephritic range proteinuria, indicated mesangioproliferative glomerulonephritis (MPGN) with immune complex deposition. The described case involves acute-on-chronic liver failure with acute insults from new onset hepatic vein thrombosis and hepatitis B reactivation, in a patient at a non-transplant center, who also had underlying antiphospholipid antibody syndrome, and MPGN. The patient was successfully treated with antiviral, anticoagulation, and antiplatelet agents, along with a sodium-glucose cotransporter 2 inhibitor and a direct intrahepatic portosystemic shunt, despite having a Model for End-Stage Liver Disease score of 35.